2022
DOI: 10.1039/d2ra03545f
|View full text |Cite
|
Sign up to set email alerts
|

Removal of methyl orange from water by Fenton oxidation of magnetic coconut-clothed biochar

Abstract: Water pollution has become a serious environmental problem to date. Advanced oxidation processes (AOP) have been widely applied in water treatments.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Xu et al suggested that the Fe particles on the surface of biochar were overlapped and piled up with each other, resulting in the reduction of the pore volume and decreasing the specific surface area. 43 The decrease in pore diameter also supported the theory that Fe particles were present within the porous structure.…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…Xu et al suggested that the Fe particles on the surface of biochar were overlapped and piled up with each other, resulting in the reduction of the pore volume and decreasing the specific surface area. 43 The decrease in pore diameter also supported the theory that Fe particles were present within the porous structure.…”
Section: Resultssupporting
confidence: 65%
“…The spectrum shows broad band at 3000-3500 cm −1 in all samples due to the presence of O-H groups. 43 For chrysanthemum, bands at 2923 and 2855 cm −1 characteristic of aliphatic C-H stretching, which supported by the presence of band at 1372 cm −1 , assigned to aliphatic C-H folding. 44 The absorption bands at 1730 and 1242 cm −1 corresponding to the stretching of carbonyl C]O and the stretching deformation of C-O and phenolic O-H groups, respectively.…”
Section: Characterisation Of Chrysanthemum and Biocharsmentioning
confidence: 80%
“…Using phosphoric acid as a solvent, the wet pyrolysis was conducted under normal pressure, with simple operation, low energy consumption, and excellent performance for cation adsorption. This study compares the KOH modified biochar, 21 phosphoric acid modification of method is more convenient. Seaweed, coconut shell, and coconut coat were all considered as excellent agro-waste, which were abundantly disposed in Hainan province without any treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, biochar has a good development prospect in ecological restoration of soil. The feedstocks and manufacturing processes of different biochar are summarized in Table 1 [31][32][33][34][35][36][37][38][39][40][41][42][43][44].…”
Section: Methods Of Soil Improvementmentioning
confidence: 99%
“…Shredded cotton stalk Slowly pyrolyzed at 450 • C under limited oxygen [31] Sugar maple and red maple Pyrolyzed at 500 • C under argon atmosphere for 30 min [33] Eucalyptus saligna leaves Pyrolyzed at 400 • C or 550 • C without steam activation [32] Paper sludge, corn stover, dried distillers grains with soluble, pinewood sawdust, cow manure, and wastewater biosolids Pyrolyzed from 600 • C to 800 • C by catalytic pyrolysis of a catalyst made at the same temperature [35] Prune residues from orchards Discontinuously pyrolyzed at 500 • C [34] Pinewood, peanut shell, and bamboo Produced by slow pyrolysis at temperatures from 300 • C to 500 • C or through hydrothermal conversion [36] Eucalyptus globulus or chopped Lantana camara stem Slowly pyrolyzed at 500 • C, and then grounded to 2 mm granules [37] Parthenium weed Pyrolyzed from 200 • C to 500 • C for 30 to 120 min [38] O. Ficus cladodes Pyrolyzed at 200 • C for 30 min, and then at 600 • C for an hour [39] The residual biomass of cultivated Gracilaria after agar extraction and Oedogonium Soaked in FeCl 3 solution for 24 h, then dried in an oven at 60 • C for 24 h, and finally slowly pyrolyzed at 300, 450, and 750 • C for 60 min [40] Eichornia crassipes Pyrolyzed with limited oxygen from 200 to 500 • C for 30 min to 2 h [41] Seaweed powder Soaked in KOH solution, then dried in an oven at 80 • C, and at last pyrolyzed at 700 • C for 270 min under the atmosphere of nitrogen [42] Tea waste Pyrolyzed at 300, 500, and 700 • C for 1 h under the condition of limited oxygen [43] 3.…”
Section: Manufacturing Process Referencementioning
confidence: 99%